The Role Of Agricultural Extensioners In Empowering Farmers (Case Study Of Pad Rice Farmers In Waitoso Village) - Lan S. Tambipessy (Cita konsultindo, 2023)
This study aims to determine the role of agricultural extension workers in empowering lowland rice farmers in Waitoso Hamlet . The analysis was performed using the SPSS descriptive test . In this study the SPSS descriptive test was used to determine the assessment obtained previously . The results showed that the role of extension workers was as a Facilitator, Motivator, and Communicator where the results of the analysis proved that there was a change in behavior in farming.